«Temeritats enlluernadores»: La ciutat en la poesia de Bartomeu Rosselló-Porcel. - BOU, ENRIC (Scripta, 2015)
Rosselló-Porcel's poetry is a work of limited extension, but of great diversity. In recent years critics have studied with precision the presence of a post-symbolist legacy. In this article I take a look at an undervalued aspect of it: the meaning and uses of urban worlds in his poetry. The poet experimented with a new concept of metaphor and incorporates elements from the urban scene using a lexicon that includes prosaic elements. Adjectives make possible the combination of description with object contemplation. The thorough analysis of three poems completes the reevaluation.